Exploring The use of Social Media on English in EFL Classes Case study : Second and Third year License Degree at University of Laghouat - Maati, Fatma; Hachani ,Siham (University of Ammar Theledji -Laghouat, 2021)
The wide spread of technology and modernity have made social media extremely important in life of the individual, especially the university student. Students of the English language tend to use social media in their academic setting in order to facilitate the learning process as well as simplifying and facilitating communication with others inside and outside the university. This study aims to investigate and highlight the impacts of using social media on the academic language English of students of the English Department at university of Amar Thlidji- Laghouat. The final results show that social media have a positive side and a negative one on their English language. From the advantages of social media we mention : facilitating learning process, prove the language, learn new vocabulary … And from its negative side, we mention wasting time and consuming energy. Health problems, lack of formality. At the end, we propose some suggestions to our dear students to benefit from this social media and to avoid the nom. Beneficial things from it . As well as our recommendation to them to use social media appropriately.